Early experience and technical aspects of physician-modified fenestration in thoracic endovascular aortic repair for aortic arch pathologies - Li, Xin (J Int Med Res, 2019)
OBJECTIVE: This study was performed to describe the treatment of aortic arch pathologies with a physician-modified fenestration (PMF) technique in thoracic endovascular aortic repair (TEVAR). METHODS: From August 2015 to August 2017, 32 patients with aortic arch pathologies underwent TEVAR with the PMF technique. All patients’ clinical data were analyzed with GraphPad Prism 7.0. RESULTS: Thirty-four aortic stent-grafts were implanted in 32 patients. The mean proximal diameter of the stent-graft was 32.4 ± 3.4 cm, and the mean length was 170.0 ± 25.2 cm. Twenty-nine PMF procedures were performed to preserve the left subclavian artery (LSA) and three to preserve both the LSA and left common carotid artery. The mean distance between the pathology and LSA was 8.4 ± 4.0 mm. The mean procedure time (from first to last digital subtraction angiography) was 22.8 ± 20.8 min. The mean follow-up time was 8.3 ± 5.3 months. During follow-up, the all-cause survival rate was 83.3% and the patency rate of the branch artery after PMF was 96.0%. CONCLUSION: The PMF technique is a relatively safe, feasible, and time-saving method to preserve the branch artery in TEVAR for aortic arch pathologies. The short- to middle-term result of this technique is satisfactory.